FOUNDATION LOCATION DETERMINATION UNDER CIMAHI MALL SOIL USING GROUND PENETRATION RADAR (GPR) WITH SHIELDED ANTENNA - Ferialdy, Armananda
Ground Penetrating Radar is geophysical method for imaging the subsurface using electromagnetic wave. Electromagnetic wave transmitted by GPR transmitter toward subsurface and reflected by material under the soil toward GPR receiver. GPR method uses electric permittivity and electromagnetic wave speed for imaging condition under the soil. This method can be used for locating foundation under the soil on construction. Cimahi Mall is currently working on leveling up their building. Therefore, they need to know the location of their foundation to continue their construction. This study use GPR with Shielded Antenna because of potential source of noise on construction location. The results of processed GPR data with Shielded Antenna will be compared to processed GPR data without Shielded Antenna. Data is processed using MatGPR software with several steps to complete, such as Dewow Filter and Removal Global Background. Based on the interpretation from processed GPR data, it is known that on each acquisition path there are 2 foundation poles with a distance of 2 meters between these poles. Processed GPR data with Shielded Antenna has a better quality than processed GPR data without Shielded Antenna.